Elements of design : Rowena Reed Kostellow and the structure of visual relationships. - Hannah, Gail Greet, ....- (New York : Princeton Architectural Press, 2002)
A hands-on book design students and designers alike will welcome. Elements of Design is a tribute to an exceptional teacher and a study of the abstract visual relationships that were her lifelong pursuit. Rowena Reed Kiostellow taught industrial design at Pratt Institute for more than fifty years and the designers she trained-and the designers they're training today-have changed the face of American design. This succinct, instructive, invaluable book reconstructs the series of exercises that led Kostellow's students from the manipulation of simple forms to the creation of complex solutions to difficult design problems. It includes her exercises and commentary along with selected student solutions, and concludes with examples of work from former students who became leaders in the field, including such well-known figures as Tucker Viemeisater, Ralph Applebaum, Ted Muehling, and many others.
Keywords: Ontwerpen